Xerxes, a new name to replace Alcantara (Asteraceae: Vernoniae) - Grant, Jason (My University, 1994)
Xerxes is proposed as a new name to replace Alcantara Glaziou ex G. M. Barroso (Asteraceae) (1969), not Alcantarea (Morren ex Mez) Harms (Bromeliaceae) (1929). The genus is monotypic, represented by Xerxes ekmanianum, comb. nov.